2012
DOI: 10.5455/vetworld.2012.103-109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Etiology of Subclinical Mastitis in Small Ruminants of Tigray Regional State, North Ethiopia

Abstract: A study was conducted at Kafta Humera and Tanqua Abergelle Districts from April to June, 2011 to assess the prevalence of subclinical mastitis in lactating small ruminants and identify bacterial causative agents. A total of 390 lactating animals comprising 255 goats and 135 sheep were randomly selected from population and screened for evidence of subclinical mastitis. The overall prevalence of subclinical mastitis was found to be 18.03% (46/255) and 28.14% (38/135) in goats and sheep, respectively. California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 2 publications
6
29
3
Order By: Relevance
“…On a udder half basis, the prevalence was 15.04%. The prevalence of caprine subclinical mastitis in other countries such as in Brazil is 22.5% (Schmidt et al, 2009), in Pakistan is 13% (Ali et al, 2010) and in Ethiopia is 18.03% (Gebrewahid et al, 2012). Recently, Islam et al, (2011) determined the prevalence of caprine subclinical mastitis in Savar area, Dhaka.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a udder half basis, the prevalence was 15.04%. The prevalence of caprine subclinical mastitis in other countries such as in Brazil is 22.5% (Schmidt et al, 2009), in Pakistan is 13% (Ali et al, 2010) and in Ethiopia is 18.03% (Gebrewahid et al, 2012). Recently, Islam et al, (2011) determined the prevalence of caprine subclinical mastitis in Savar area, Dhaka.…”
Section: Discussionmentioning
confidence: 99%
“…All the tested isolated bacterial species were found highly sensitive to broad spectrum antibiotics such as amoxicillin, chloramphenicol, ciprofloxacin and tetracycline suggesting that these antibiotics could be the first choice of drug for the treatment purpose. Many authors reported antibiotic resistant strains of S. aureus as the dominant bacterial species frequently isolated from milk samples collected from subclinical caprine mastitis (Mhase et al, 2007;Ali et al, 2010;Gebrewahid et al, 2012). In addition, Islam et al (2011) found S. aureus as the major etiological agent for subclinical mastitis in goat in Savar area of Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of somatic cells in milk is a good indication of inflammation as shown in Table 2 which indicates that the majority of ewes react to Science Publications AJAVS infecting bacteria by raising the somatic cells in milk. So the CMT is a useful screening test in the detection of mastitis and may serve to segregate mammary glands infected with major pathogens in a subclinical form (Schuppel and Schwope, 1998;Clements et al, 2003;Gebrewahid et al, 2012). Table 1 and 2 indicated that bacterial infection was involved in mastitis of ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in different parts of the world have been conducted for the assessment of the occurance of clinical and subclinical mastitis in different breeds of sheep (Al-Majali and Jawabreh, 2003;Contreras et al, 2007;Gebrewahid et al, 2012). The relation among CMT, the presence of inflamed udders and the bacteriological findings indicated that ewe milk is like that of cows and camels (Djabri et al, 2002;Hawari and Al-Dabbas, 2008); it also indicated that ewes have phogocytic cells, which constitute one of the essential defences against microbial infection of the mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that the epidemiology of mastitis caused by CoNS is complex in goats, which is expected, since this group is represented by a large range of species with different pathogenic traits. Indeed, CoNS are the most frequent mastitis-causing agents in lactating goats [8,[11][12][13].…”
Section: S Epidermidis -mentioning
confidence: 99%